Analysis of the STP Marketing Strategy for Handmade Knitwear Products in MSMEs (Case Study on Candyco_id MSME) - Khusnia, Rif’atul; Sudarmiatin; Handayati, Puji; Suharsono, Naswan (CV. Lenggogeni Data Publishing, 2025)
This research aims to analyze the Segmenting, Targeting, and Positioning (STP) based marketing strategy for Candyco_id, a handmade knitting craft business in Malang City. This research uses a qualitative method with a case study approach to deeply explore the experiences of business owners thru interviews, observations, and an examination of marketing activities. The research findings indicate that the application of STP at Candyco_id evolved naturally and adaptively, influenced by direct interaction with consumers and social media trends. Market segmentation is formed based on demographic, geographic, psychographic, and behavioral characteristics, with gift-giving motives and a unique preference for handmade products being dominant. The targeting is directed toward students as the primary segment, with expansion thru digital marketing reaching consumers outside the region and potentially entering international markets. Positioning is built thru the differentiation of custom services, quality craftsmanship, and storytelling that strengthens the emotional value of the product. The challenges faced include price wars, which highlight the need for consumer education about the value of craftsmanship. Overall, this research confirms that the STP strategy plays an important role in strengthening the competitiveness of handmade creative MSMEs and can serve as a reference for developing marketing strategies in similar sectors.